2010
DOI: 10.1063/1.3309489
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation uniformity and zooming performances for a capsule directly driven by a 32×9 laser beams configuration

Abstract: An inertial confinement fusion capsule directly driven by laser beams has been considered. A ray-tracing package is used to evaluate the uniformity of the energy deposition and the absorption efficiency provided by the direct irradiation of the capsule. Two distinct configurations with a single laser beam or a bundle of nine laser beams associated to 32 directions of irradiation are considered. Assuming a beam-to-beam power imbalance of 5% and a super-Gaussian spatial profile of the beams intensity, is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…These beamlets should be grouped in bundles which surface would be of about 1 -1.5 m 2 (which is roughly the double of a quad in the National Ignition Facility [12] in the USA or the Láser MegaJoule [13] . Moreover, the large number of beamlets is also useful in order to use the zooming technique [14] where different focal spots are used to optimize the laser-capsule coupling preserving the irradiation uniformity of the capsule [15]. In this paper we analyze the illumination nonuniformity of a spherical capsule directly irradiated by a large number of láser beams affected by unavoidable beam imperfections.…”
Section: Introductionmentioning
confidence: 99%
“…These beamlets should be grouped in bundles which surface would be of about 1 -1.5 m 2 (which is roughly the double of a quad in the National Ignition Facility [12] in the USA or the Láser MegaJoule [13] . Moreover, the large number of beamlets is also useful in order to use the zooming technique [14] where different focal spots are used to optimize the laser-capsule coupling preserving the irradiation uniformity of the capsule [15]. In this paper we analyze the illumination nonuniformity of a spherical capsule directly irradiated by a large number of láser beams affected by unavoidable beam imperfections.…”
Section: Introductionmentioning
confidence: 99%
“…In the LMJ facility, the laser beams are grouped in quads; thus the power imbalance benefits from a statistical factor which reduces it to σ PI = 5% (quad-to-quad). The illumination non-uniformity, evaluated taking into account these beam uncertainties, is usually measured as an average value (σ ) estimated over a large number of calculations [72][73][74][75][76][77] . In these calculations, each of the three parameters (laser power, laser pointing, and target position) varies randomly and follows a Gaussian distribution centred to their nominal values and characterized by the corresponding standard deviation σ PI , σ PE , or σ TP .…”
Section: Illumination Non-uniformitymentioning
confidence: 99%
“…Included in the design as a mandatory requirement is the use of a phase plate to both condition the focal spot and create the necessary stationary speckle pattern. This bundle design has many advantages when considering focal spot conditioning, optical zooming, and pulse shaping; it has been described in detail in [22][23][24] . Both NIF and LMJ have shown that in solid-state lasers, the bandwidth is large enough to withstand phase modulation as a necessary requirement for beam smoothing and stimulated Brilloouin scattering (SBS) suppression.…”
Section: Laser Design: Architecturementioning
confidence: 99%